HUBUNGAN KOMUNIKASI DAN BUDAYA ORGANISASI DENGAN KINERJA PEGAWAI PADA DINAS TANAMAN PANGAN HORTIKULTURA DAN PERKEBUNAN PROVINSI BENGKULU - Asmawi Jaya; Rinto Noviantoro (Universitas Dharma Andalas, 2019)
The aim of this research is to know the relationship communication with performance of employee at Dinas Tanaman Pangan Hortikultura and Perkebunan Bengkulu Province and to know the relationship organizational culture with performance of employee at Dinas Tanaman Pangan Hortikultura and Perkebunan Bengkulu Province. Method Analysis used correlation of spearman rank and hypothesis test. Pursuant to result of research obtained by correlation coefficient value beetween communication with performance of employee by value of rho count = 0,859 its meaning the relationship of communication with performance of employee at Dinas Tanaman Pangan Hortikultura and Perkebunan Bengkulu Province is very strong, because correlation value reside in coefficient interval 0,800 - 1,000. For the test of hypothesis obtained by value of t count > t tables ( 11,605 > 1,677), its meaning there are relation of significant between Performance of employee at Dinas Tanaman Pangan Hortikultura and Perkebunan Bengkulu Province. Pursuant to result of research obtained by correlation coefficient value beetween organizational culture with performance of employee by value of rho count = 0,859 its meaning the relationship of organizational culture with performance of employee at Dinas Tanaman Pangan Hortikultura and Perkebunan Bengkulu Province is very strong, because correlation value reside in coefficient interval 0,800 - 1,000. For the test of hypothesis obtained by value of t count > t tables (9,232 > 1,677), its meaning there are relation of significant between organizational culture with performance of employee at Dinas Tanaman Pangan Hortikultura and Perkebunan Bengkulu Province